(untitled) (International journal of artificial intelligence, 2024)
This article describes the scientific-theoretical foundations of tourism development, further increasing the competitiveness of tourism, improving the quality of the provided tourist services, the development trends of tourism in Uzbekistan and suggestions for the development of tourism are presented.